Types of alcoholic beverages and blood lipids in a French population. Issue 1 (1st January 2002) - Ruidavets, J-B; Ducimetiére, P; Arveiler, D; Amouyel, P; Bingham, A; Wagner, A; Cottel, D; Perret, B; Ferriéres, J
Abstract : Study objective: Prospective studies have shown a consistent relation between alcohol consumption and decreasing incidence of coronary artery disease. The protective effect of alcohol could be mediated through increased levels of HDL cholesterol (HDL-c). The aim of this study was to examine the relation between blood lipid levels and the consumption of different types of alcoholic beverages among 1581 men and 1535 women. Design: Data from representative cross sectional surveys (1994–1997) in three different regions of France were used. The consumption of the different types of alcohol was quantified using a recall method according to a typical weekly consumption. Main results: The median daily alcohol intake was 24 g for men and 4 g for women. After adjustment for confounders, total alcohol showed a positive and significant association with HDL-c and triglycerides (TG) in both sexes. In multivariate analysis, wine was positively associated with HDL-c. Beer was positively associated with HDL-c in men and with triglycerides in men and women. When taking drinking patterns into account, wine drinkers had higher HDL-c levels than non-wine drinkers. Differences became non-significant after adjustment for confounders and particularly for socioeconomic parameters. Conclusions: In a French population sample, total alcohol was positively associated with HDL-c and triglycerides. The specific influence of any particular alcoholic beverage on blood lipids was not clearly demonstrated but wine preference found in a group with higher lifestyle standards was associated with a more favourable blood lipid profile.